The Constitutional Basis of Religious Pluralism in the United States: Causes and Consequences - Jelen, Ted G. (The annals of the American Academy of Political and Social Science, 2007)
In this article, the author attempts to show how provisions in the U.S. Constitution enhance religious pluralism in the United States. Furthermore, religious pluralism arguably leads to religious vitality, which has a number of consequences for public life in the United States. Religion in the United States serves as a source of social capital, as a check against the conformist tendencies of U.S. public opinion; religious pluralism ameliorates the tendency to identify the nation with a particular set of religious traditions. The presence of religious ideas in public discourse also may render religious values less particularistic and more publicly accessible.